Neutrophils and Malaria - Aitken, Elizabeth H.; Alemu, Agersew; Rogerson, Stephen J. (Frontiers in Immunology, 2018)
Neutrophils are abundant in the circulation and are one of the immune system’s first lines of defence against infection. There has been substantial work done investigating the role of neutrophils in malaria and it is clear that during infection neutrophils are activated and are capable of clearing malaria parasites by a number of mechanisms. This review focuses on neutrophil responses to human malarias, summarising evidence which helps us understand where neutrophils are, what they are doing, how they interact with parasites as well as their potential role in vaccine mediated immunity. We also outline future research priorities for these, the most abundant of leukocytes.